Determination of the possibilities of using the universal low-temperature rotary apparatus for the production of meat and vegetable products under the conditions of providing uniform heat supply - Zahorulko, Andrii; Zagorulko, Aleksey; Tytarenko, Nataliia; Ibaiev, Eldar; Zahorulko, Vitaly (Technology audit and production reserves, 2024)
The object of research is the process of frying a meat-vegetable product in the developed universal low-temperature rotary apparatus. The problem of ensuring the uniformity of the temperature field during low-temperature processing of meat and vegetable products is solved in the developed universal low-temperature rotary apparatus. The expected effect during the approbation of the apparatus is predicted under the condition of eliminating high-temperature intermediate coolants (hot air, etc.) due to the use of a film-like resistive electronic heater of the radiating type. The temperature field is established, which confirms the uniformity of the temperature effect on meat and vegetable products, and a slight deviation within the limits of autonomous exhaust fans is not critical and within the permissible error. Also, the introduction of Peltier elements into the design of the rotary apparatus will allow converting thermal energy into a low-voltage supply voltage (3–6 W) and, already at 20 °C, ensure autonomous operation of fans. The obtained results in the form of practical implementation of the developed apparatus will allow to implement low-temperature processing of meat and vegetable products. This allows to maximally preserve the functional properties of meat raw materials and the physiological properties of vegetable semi-finished products with a high degree of readiness. The practical implementation of the universal low-temperature rotary apparatus from the side of constructive implementation due to the use of functional containers makes it possible to obtain a wide range of assortment of meat products, both in the shell and without the shell. The elimination of high-temperature intermediate heat carriers (hot air, steam, etc.), their technical networks and generating apparatuss ensures energy and metal-intensive resource savings. In addition, the introduction of multicomponent vegetable semi-finished products of a high degree of readiness (powders, pastes, etc.) into the recipes of meat products will lead to a partial replacement of the main recipe components and an increase in the functional properties of the finished products.